THE STRUCTURE OF CARBOXYPEPTIDASE A, IX. THE X-RAY DIFFRACTION RESULTS IN THE LIGHT OF THE CHEMICAL SEQUENCE - Lipscomb, William N. (1969)
Several features of carboxypeptidase A (CPA) which were previously established by the X-ray diffraction structure studies have now been confirmed by the chemical sequence analysis. These results include the number (307) of amino acid residues in CPA(α), the identities of the residues (Arg 145, Glu 270, and Tyr 248) shown by the X-ray study to be involved in substrate binding and catalysis, and the existence of a disulfide bond. The Zn ligands, shown by the X-ray study to be residues 69, 72, and 196 and identified as His, Glx, and either Glx or Lys, are proved by the chemical sequence to be His, Glu, and His, respectively. No change is required in our previous mechanistic deductions, which are here extended to include a specific mechanism of activation of the substrate by a net charge on the metal ion, which suffers a change in local dielectric constant when it is covered by a substrate.